Features of morphometric parameters of vessels in the human portal venous system identified by multislice computed tomography - A. N. Russkikh; A. D. Shabokha; N. V. Tyumentsev; S. N. Derevtsova (Бюллетень сибирской медицины)
The aim of this study was to identify the morphometric features of the human portal venous system by means of multislice computed tomography (MSCT).Materials and methods. A contrast X-ray study of the portal vein was carried out in 53 men who were treated in the surgical departments of the Krasnoyarsk Regional Hospital No. 1. The average age of the patients was 54.9 ± 1.7 years (36–71 years). Measurements were performed on 3D models of the vascular bed in the portal venous system (GE Advantage Workstation and Siemens singo.via workstations). Branching patterns, length, diameter, angle of the portal vein formation relative to the midline of the human body, and angles of formation of the vessels forming the portal vein in the frontal plane were evaluated.Results. Variations in the morphometric parameters of the intrahepatic vessels of the portal vein are obvious, although the branching patterns are not diverse and are reduced to one type – the magistral pattern (according to V.N. Shevkunenko). The veins that form the portal vein are represented by three systems, each of which has a stem and tributaries that differ in branching patterns and other morphological characteristics.Conclusion. The findings of the study made it possible to supplement the scientific materials regarding branching patterns and morphological characteristics of the portal vein and its tributaries as well as to use the morphometric characteristics of the superior and inferior mesenteric and splenic veins to resolve the issues of surgical intervention on the abdominal organs.